2020
DOI: 10.22216/jbe.v5i2.5303
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Manajemen Perubahan, Kepemimpinan Transformasional, Struktur Organisasi, Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan

Abstract: <p><em>Employee performance is an interesting topic researched, because employee performance determines organizational sustainability. This study analyzes the effect of: Change Management on employee performance, Transformational Leadership on employee performance, Organizational Structure on employee performance, Organizational Culture on employee performance, Work Discipline on Employee Performance, and analyzing the effects of change management, transformational leadership, organizational struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
(3 reference statements)
1
4
0
3
Order By: Relevance
“…The results of the above study are in accordance with research conducted by Thomas Ratnasari et al [9], Harahap [10] who found that effective change management practices will have a positive impact on performance. In addition, research conducted by Wiezer et al [13] that not all changes have a negative effect, changes that are planned and managed effectively have an effect on increasing better welfare, this is due to the perception of security felt by employees or employees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the above study are in accordance with research conducted by Thomas Ratnasari et al [9], Harahap [10] who found that effective change management practices will have a positive impact on performance. In addition, research conducted by Wiezer et al [13] that not all changes have a negative effect, changes that are planned and managed effectively have an effect on increasing better welfare, this is due to the perception of security felt by employees or employees.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research conducted by Thomas [3], Wanza & Nkuraru [4], Menda et al [5], Kahoro & Rugami [6], Kojo et al [7], Kimhi et al [8], Ratnasari et al [9], Harahap [10] found that the implementation of effective change management in all sectors has a significant positive impact on employee performance. In contrast to the research conducted by Mudeng et al [11] which found that organizational change had no significant effect on employee performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Penelitian sebelumnya yang dilakukan oleh (Thomas, 2014;Wanza & Nkuraru, 2016;Menda et al, 2018;Kahoro & Rugami, 2018;Kojo et al, 2019;Kimhi et al, 2019;Ratnasari et al, 2020;Harahap, 2020) menemukan bahwa implementasi manajemen perubahan yang efektif dalam seluruh sektor memberikan dampak positif yang signifikan bagi kinerja pegawai. Berbeda dengan penelitian yang dilakukan Mudeng et al, (2017) yang menemukan bahwa perubahaan organisasi tidak berpengaruh signifikan pada kinerja karyawan.…”
Section: Penghapusan Jabatan Eselon III Dan Iv Telah Diserukan Kement...unclassified
“…Tabel 11 merupakan hasil uji hipotesis pada penelitian ini. Hasil penelitian, sesuai dengan penelitian yang dilakukan oleh (Thomas, 2014;Wanza & Nkuraru, 2016;Menda et al, 2018;Kahoro & Rugami, 2018;Kojo et al, 2019;Kimhi et al, 2019;Ratnasari et al, 2020;Harahap, 2020) Penelitian selanjutnya disarankan untuk dapat mengeksplorasi variabel-variabel lain yang mungkin dapat memengaruhi dan mensukseskan perubahan yang direncanakan seperti peran kepemimpinan (Faupel & Süß, 2019). Selain itu peneliti selanjutnya dapat menjadikan penelitian ini sebagai referensi untuk dapat mengetahui dampak perubahan jabatan khususnya pada institusi pendidikan tinggi atau dapat menerapkannya pada objek penelitian lainnya dengan sektor yang berbeda.…”
Section: Uji Hipotesisunclassified
“…Organizational structure is a description that describes the type of organization, organizational departments, positions, types of authority of officials, fields and work relations, lines of command, responsibility responsibilities, the span of control, and leader system of the organization (Ratnasari et al, 2020). Organizational structure can be defined as a formal organizational framework in which work tasks are divided, grouped, and coordinated (S. Robbins & Timothy, 2008) According to Kates & Galbraith (2007), the organizational structure is the process of reviewing and configuring individual or individual structures, processes, reward systems, and activities to create an effective organization that can achieve business strategy.…”
Section: Introductionmentioning
confidence: 99%